The "God of Israel" in History and Tradition - Stahl, Michael J., (Vetus Testamentum, Supplements ;, 2021)
In The "God of Israel" in History and Tradition , Michael Stahl provides a foundational study of the formulaic title "god of Israel" ( 'elohe yisra'el ) in the Hebrew Bible. Employing critical theory on social power and identity, and through close literary and historical analysis, Dr. Stahl shows how the epithet "god of Israel" evolved to serve different social and political agendas throughout the course of ancient Israel and Judah's histories. Reaching beyond the field of Biblical Studies, Dr. Stahl's treatment of the historical and ideological significances of the title "god of Israel" in the Hebrew Bible offers a fruitful case study into the larger issue of the ways in which religion may shape-and be shaped by-social and political structures.